Predisposition Towards Sustainable Behaviour Among Students in the Pre-school Education Study Programme - Šindić, Aleksandra; Barbarev, Kiril; Gavriloski, Marko; Lepičnik Vodopivec, Jurka (Revija za elementarno izobraževanje, 2021)
Starting from the importance of sustainable behaviour among educators for sustainability in kindergarten, the aim of this empirical quantitative study was to investigate the prevalence of predispositions towards sustainable behaviour among students from the first cycle of the Preschool Education study programme at three universities. The connection between predispositions, the existence of a difference between cognitive and non-cognitive predispositions, and the absence of a statistically significant difference between the predispositions of the students in relation to home faculty and place of residence were determined.